HUBUNGAN FASILITAS BELAJAR DENGAN HASIL BELAJAR BAHASA INDONESIA SISWA KELAS X SMKN 1 KECAMATAN LUAK KABUPATEN LIMA PULUH KOTA - Poni Ernis (Menara Ilmu, 2018)
This research is motivated by student learning facilities that less than the maximum. Studentsare not focused and are more likely to play around when the teacher explains the lesson sothat the interaction between teacher and student does not go well. Student learning facilitiesthat are less than the maximum will affect student learning outcomes. This study aims todescribe the relationship of learning facilities with student learning outcomes class X SMKN 1District Luak Lima Puluh Kota. The type of research is quantitative research usingcorrelational descriptive method. The population in this study were the students of class Xconsisting of seven classes with the number of 112 people and the sample of the study wastaken by using cluster random sampling technique of 31 people, class X pemasara 2. Thisstudy used two variables, the variable (X) learning facilities, and Variable (Y) result oflearning Indonesian. The steps of data analysis as follows. (1) Correcting and tabulating thequestionnaire value; (2) Provide a score on each question; (3) Score the results of the firstsemester Indonesian exam; (4) Grouping values by rating scale; (5) Correlate data onlearning facilities with learning outcomes; (6) Hypothesis testing; (7) Summing up the resultof data analysis. The results showed that the average learning facility is 81 with goodqualification and average learning outcome is 81 with good qualification. Furthermore, thetest using the formula product moment obtained rhitung 0, 2903 and titung 2.678 with degreesof freedom n-2 (31-2 = 29), and a significant level of 0.05. Hypothesis accepted if thitung>ttable. Thus H1 is accepted because the test results prove that t count is greater than ttablethat is 2.678> 1.699. It can be concluded that there is a significant relationship betweenlearning facilities with learning outcomes Indonesian class X marketing students 2 SMKN 1District Luak District Lima Puluh Kota.Kata kunci : fasilitas belajar, hasil belajar